2016
DOI: 10.1101/050237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal assessment of sputum microbiome by sequencing of the 16S rRNA gene in non-CF bronchiectasis patients

Abstract: 2Bronchiectasis is accompanied by chronic bronchial infection that may drive disease progression.3 However, the evidence base for antibiotic therapy is limited. DNA based methods offer better 4 identification and quantification of microbial constituents of sputum than standard clinical culture and 5 may help inform patient management strategies. Our study objective was to determine the longitudinal 6 variability of the non-CF bronchiectasis microbiome in sputum with respect to clinical variables. 7 Eighty-five… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…A version of this manuscript was archived on the pre-print server BioRxiv[ 11 ] and some of the data was presented at the American Thoracic Society Conference[ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A version of this manuscript was archived on the pre-print server BioRxiv[ 11 ] and some of the data was presented at the American Thoracic Society Conference[ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some of this work has been presented before in the form of an abstract and presentation at the American Thoracic Society International Conference 2015 [ 10 ] and pre-print at BioArxiv.org [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…Triplicate 10 μl qPCR reactions were set up containing 1 μl of bacterial DNA and 9 μl of Femto™ bacterial qPCR premix (Cambridge bioscience, UK). Each run contained a 10-fold dilution series of the Vibrio natriegens DSM 759 gene cloned into a plasmid of known size and a nontemplate control [14]. For data acquisition, the following cycling parameters were used: 1…”
Section: S Quantitative Pcrmentioning
confidence: 99%
“…Changes in the respiratory microbiome have been associated with the clinical, physiological and therapeutic aspects of chronic lung diseases such as asthma, bronchiectasis, chronic obstructive pulmonary disease (COPD) and IPF [12][13][14][15][16][17][18]. Studies of the respiratory microbiome in IPF have reported associations between changes in microbial communities, disease progression and mortality [16,17,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The structure of microbial communities is highly individual between patients, and may relate weakly to disease state or antibiotic exposure [21]. The administration of prophylactic treatment with oral erythromycin (macrolide) therapy for one year, for example, demonstrated a decrease in H. influenzae and an increase in P. aeruginosa communities by lung microbiome analysis in patients without culture proven P. aeruginosa at baseline [22].…”
Section: Microbiological Developmentsmentioning
confidence: 99%